Pneumotoraks Katamenial: Patofisiologi, Diagnosis, dan Tata Laksana - Angelina Patricia Chandra; Reynardi Larope Sutanto; Averiell Larope Sutanto (PT Kalbe Farma Tbk., 2024)
Catamenial pneumothorax is a rare condition in the spectrum of thoracic endometriosis syndrome (TES), women of reproductive age experience spontaneous pneumothorax episodes that occur around the time of menstruation. Although infrequent, cases of recurrent pneumothorax accompanied by a history of pelvic surgery, menstrual pain, and infertility should raise clinical suspicion. Diagnosis involves a comprehensive history, radiological examination, and video laparoscopy as the definitive diagnostic method. Management includes symptomatic management with pleural drainage, followed by minimally invasive operative therapy and hormonal therapy for 6-12 months post-initial management. The recurrence of catamenial pneumothorax remains a problem, and its prognosis and impact are not yet fully understood.